Confini e frontiere nell’Etruria nordorientale - Camilla Zeviani (Frontière·s)
Boundaries are symbols of identity construction and preservation, which is a current theme in anthropological literature. To show how such notions can be applied to ancient contexts, this article offers an interpretation of boundary stones found in north-east Etruria, a region considered a frontier between different cultural entities. The Etruscan frame of mind has always been boundary oriented. The threat represented by ‘the other’, ignited by the Gallic invasions and Rome’s rising military force in the 4th century BCE, reinforced such traditional and embedded world views. It encouraged the powerful north-eastern centres of Perugia, Cortona and Fiesole to invest in boundary construction to assert family and ‘national’ identity against this ‘other’. These boundary stones were a response to the effects of Roman military advances and to the identity crisis that stemmed from the social and economic ties Etruria had with Rome. Indeed, the stones were linked to the old landowning system and symbolised a long-lasting Etruscan identity, made of religious and cultural practices and tradition. Furthermore, the sacred signification of these pillars was made clear by the inscription of the word tular.